A autonomia municipal na federação brasileira : a teoria da subsidiariedade entre o constitucionalismo e as relações de poder na Constituição de 1988 - Silva, Fernando Carlos Dilen da (2008)
This dissertatoin analyze the law´s structure of brasilian´s cities beggining from the elaboration of the first republican´s constitution, inspired by the north american´s federalism and the formal inclusion from these cities as federative member. With this analyse, it´s gonna be setting these formals directives of the Constitutions from years 1891, 1934 1937, 1946 e 1967-69 with the politicals systens that by force vigorates on that periods, confirmatin, or not, this tension (and the consequences) between rights and politics. This new interpretation of those citiy´s autonomies on Constitution is gonna be fundamented on haberman´s theory about his conception of a righ being created discursivaly, and the Principle of Subsidiarity, used here as a way for better discrimination of competences between the Federation´s entity. This principle defends that the bigger entity can´t realize the interests from the lowerr entitiy when this last could realize as itself, or without help. The nacional and the regional entities must execute their political public acting subsidiary, coordenating or helping the local entities. It gonna be analysed also the registries from the Nacional Constituition on Brazil during from 1986 untill 1988, influenciated by the municipalism and from the historical context for a bigger political descentralization. The meaning is otimizate the local autonomies that, defined by the Constitution of 1988 as legitimation of a bigger local Power, can stay near from the comunities of popular particiipations. By this way, it could be possible a better adoption from these deliberative discursive procedures like seminaries and public consultants, alredy realized on some brasilian´s cities. Concluding it gonna be made some criticals about the configuration of the Brazil´s federalism, priorizating the action of the cities on creation and realization from the publics politicals localized.